Hearing Preservation in Pediatric Cochlear Implantation. Issue 6 (July 2017) - Carlson, Matthew L.; Patel, Neil S.; Tombers, Nicole M.; DeJong, Melissa D.; Breneman, Alyce I.; Neff, Brian A.; Driscoll, Colin L. W.
Abstract : Objective: Currently, there is a paucity of literature evaluating hearing preservation outcomes in children following cochlear implantation. The objective of the current study is to report pediatric hearing preservation results following cochlear implantation with conventional full-length electrodes. Study Design: Retrospective review (2000–2016). Setting: Tertiary referral center. Patients: All pediatric patients with a ⩽ 75 dB preoperative low-frequency pure tone average (LFPTA; 250–500 Hz average), who underwent cochlear implantation with a conventional length electrode. Intervention(s): Cochlear implantation. Main Outcome Measure(s): Complete, partial, minimal, or no hearing preservation following cochlear implantation (Skarzynski et al., 2013); maintenance of functional low frequency hearing (⩽85 dB LFPTA). Results: A total of 43 ears, in 35 pediatric patients, met inclusion criteria. The mean age at time of implantation was 8.6 years (range, 1.4–17.8 yr), 20 (57.1%) patients were female, and 25 (58.1%) cases were left-sided. The mean preoperative ipsilateral low frequency PTA and conventional four-frequency PTA (500, 1000, 2000, 3000 Hz average) were 54.2 dB (range, 15–75 dB) and 82.2 dB (range, 25–102.5 dB), respectively. The mean low frequency PTA and conventional four-frequency PTA shifts comparing the pre- and first postoperative audiogram were Δ25.2 dB (range, −5 to 92.5 dB) and Δ18.3 dB (range, −8.8 to 100 dB), respectively. Overall, 17 (39.5%) ears demonstrated complete hearing preservation, 19 (44.2%) ears partial hearing preservation, 0 minimal hearing preservation, and 7 (16.3%) exhibited no measurable acoustic hearing after surgery. In total, 28 (65.1%) ears maintained functional low-frequency hearing (i.e., ⩽85 dB LFPTA) based on the initial postoperative audiogram. There was no statistically significant difference in the initial low frequency PTA shift comparing lateral wall and perimodiolar electrodes (Δ22.2 versus Δ28.1 respectively; p  = 0.44), cochleostomy and round window insertions (Δ25.2 vs. Δ24.7 respectively; p  = 0.95), or statistically significant association between age at implantation and low frequency PTA shift ( r  = 0.174; p  = 0.26). In total, 22 ears in 19 patients had serial audiometric data available for review. Over a mean duration of 43.8 months (range, 2.6–108.3 mo) following surgery, the mean low frequency PTA and conventional four-frequency PTA shift comparing the initial postoperative and most recent postoperative audiogram was Δ9.7 dB (range, −27.5 to 57.5 dB) and Δ8.1 dB (range, −18.8 to 31.9 dB), respectively. Conclusions: Varying levels of hearing preservation with conventional length electrodes can be achieved in most pediatric subjects. In the current study, 82% of patients maintained detectable hearing thresholds and 65% maintained functional low-frequency acoustic hearing. These data may be used to guide preoperative counseling in pediatric patients with residual acoustic hearing. Additionally, the favorable rates of hearing preservation achieved in children provide further evidence for the expansion of pediatric cochlear implant candidacy to include patients with greater degrees of residual hearing.